Structural elucidation and immunostimulatory activity of a new polysaccharide from Cordyceps militaris. Issue 1 (23rd November 2017) - Bi, Sixue; Jing, Yongshuai; Zhou, Qinqin; Hu, Xianjing; Zhu, Jianhua; Guo, Zhongyi; Song, Liyan; Yu, Rongmin
Abstract : The chemical structure of new polysaccharide (CMPB90-1) obtained from Cordyceps militaris was elucidated, and its strengthening effects on immunostimulatory activities of lymphocytes and inducing effects on M1 polarization of macrophages were evaluated. Abstract : A new polysaccharide (CMPB90-1) was isolated from cultured Cordyceps militaris by alkaline extraction. The chemical structure of CMPB90-1 was determined by analysis of physicochemical and spectral data. The backbone of CMPB90-1 is composed of (1→6)-linked α-d -glucopyranosyl and (1→3)-linked α-d -glucopyranosyl residues, with branching at O-6, which consists of (1→4)-linked β-d -mannopyranosyl and (1→6)-linked α-d -glucopyranosyl residues, respectively. β-d -Galactopyranosyl residues is the terminal unit. In vitro immunomodulatory assay revealed that CMPB90-1 promoted proliferation of splenic lymphocytes, enhanced cytotoxicity of NK cells and promoted lymphocyte secretion of the cytokine interleukin-2. Besides, CMPB90-1 upregulated T-cell subpopulation, strengthened phagocytosis function of macrophages and induced their M1 polarization. The mechanism of the effects might be due to the activation of TLR2, MAPK and NF-κB pathways. The results proposed that CMPB90-1 can be researched and developed as a new functional food.